17 A De novo Recessive Mutation Causative of Mandibulofacial Dysostosis in Hereford Cattle. (7th May 2021) - Sieck, Renae L; Fuller, Anna M; Bedwell, Patrick; Ward, Jack; Sanders, Stacy; Xiang, Shi-Hua; Peng, Sichong; Steffen, David; Petersen, Jessica L
Abstract: In spring 2020, six Hereford calves presented with congenital craniofacial abnormalities attributed to a condition we termed mandibulofacial dysostosis (MD). Pedigree analysis revealed a single common ancestor shared by the sire and dam of each affected calf. We hypothesized that MD in Hereford cattle is attributed to a de novo mutation with an autosomal recessive mode of inheritance. To avoid production of affected calves, the objective of this study was to identify the cause of MD. Whole-genome sequencing (WGS) of 20 animals (3 affected, 7 obligate carriers, 10 related) yielded 143 variants matching the hypothesized mode of inheritance. Genotyping of 2 additional affected calves, 760 Herefords, and evaluation of WGS data from over 2, 500 other individuals led to the discovery of a missense mutation (Chr26 g. 14404993 T >C) in CYP26C1 associated with MD. The amino acid change due to the CYP26C1 variant (p. L188P) is located in an α helix of the protein; modeling suggests the substitution breaks the helix. The mutation is predicted to be deleterious (SIFT = 0) and is otherwise conserved across species. In our data, all heterozygotes had at least one pedigree tie to the suspect founder. CYP26C1 plays a vital role in tissue-specific regulation of retinoic acid (RA) during embryonic development. Dysregulation of RA can result in teratogenesis by altering the endothelin-1 signaling pathway affecting the expression of Dlx genes, critical to mandibulofacial development. Further, multiple human conditions with similar pathologic characteristics are attributed to dysfunction of this gene and/or retinoic acid signaling. We conclude that this recessive missense mutation in CYP26C1 impacts the catalytic activity of the encoded enzyme, leading to excess RA and resulting in the MD phenotype. Breeders can now genotype their animals to identify carriers. These data also contribute to expanding the understanding of craniofacial development across species.